2007
DOI: 10.1007/s11255-006-9051-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis in dialysis patients: association of tuberculin and 2,4-dinitrochlorobenzene reactivity with risk of tuberculosis

Abstract: Anergy distorts the association of tuberculin reactivity with risk of TB. Anergic dialysis patients are at increased risk of developing active TB and chemoprophylaxis is justified in them too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Biological factors, such as advanced age and low BMI, are factors of immunological imbalance that influenced CMI responses of HD patients [24]. However, female HD patients enrolled in this study demonstrated a higher prevalence and risk of TB, even after allowing for the effect of the abovementioned factors.…”
Section: Discussionmentioning
confidence: 68%
“…Biological factors, such as advanced age and low BMI, are factors of immunological imbalance that influenced CMI responses of HD patients [24]. However, female HD patients enrolled in this study demonstrated a higher prevalence and risk of TB, even after allowing for the effect of the abovementioned factors.…”
Section: Discussionmentioning
confidence: 68%
“…A common finding associated with uremia is impaired immunity, including disorders of Tlymphocyte growth and activation, lymphopenia and decreased antigen-specific humoral immunity mediated by Tlymphocytes (12). In addition, several factors specific for HD patients, such as malnutrition, anemia, vitamin D deficiency and hyperparathyroidism, may further contribute to impaired immunity (13)(14)(15)(16). Therefore, HD patients are considered to have high susceptibility to TB, and latent TB is 52.5 times more likely to be reactivated in patients with renal failure than in the general population (1,17).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the IGRA conversion/ reversion and the preexisting risk for LTBI was also analyzed by adjustment to the other risk factors such as age, sex, duration of hemodialysis, diabetes mellitus, and the previous BCG vaccination using multivariate logistic regression analysis. 19 Variables for which the p value was less than 0.200 in the univariate analysis were included in the final model of the multivariate analysis. The agreement among test results was assessed using k coefficients.…”
Section: Discussionmentioning
confidence: 99%